Assessing Prevalence, Risk Factors, and Occupational Impact of Voice Disorders Among Teachers: A Population-Based Survey in Aseer Region, Saudi Arabia - Hayfa Alhefdhi; Mona Aldukain; Ali Aldukain; Norah Saad Jadaan; Roaa Al Murayyi; Seham Marei Alqahtani; Ruba Al Murayyi; Abdusalam Saad Alqhtani; Khalid Abdulaziz Alshahrani; Bander Mahfouz Alaamri (The Egyptian Journal of Otolaryngology)
Abstract Background Voice disorders are a significant occupational concern for teachers, whose work relies heavily on vocal communication. These disorders, which include symptoms such as hoarseness, vocal fatigue, and discomfort, can affect both professional performance and quality of life. Teachers are particularly vulnerable due to the demanding nature of their profession, including prolonged speaking hours, large class sizes, and noisy classroom environments. While the prevalence of voice disorders among teachers is well-documented globally, limited data is available from regions like the Aseer region of Saudi Arabia. This study aims to assess the prevalence, identify risk factors, and evaluate the impact of voice disorders among teachers in Aseer, providing a basis for targeted interventions. Methods A cross-sectional survey of 370 teachers was conducted using the validated Arabic Voice Handicap Index-10 (VHI-10). Data on demographics, vocal symptoms, risk factors, and impacts were collected via an online questionnaire. Statistical analysis included descriptive statistics and Fisher’s exact tests to evaluate associations. Results Over 60% of participants reported voice-related symptoms, primarily hoarseness and vocal fatigue. Classroom noise levels, prolonged vocal use, and large class sizes were significant risk factors. Few teachers (5.1%) had a formal diagnosis, and most (75.4%) did not seek treatment. Voice disorders adversely affected teaching performance and student interactions, with a subset reporting work absenteeism and emotional distress. Conclusions Voice disorders are common among teachers in the Aseer region and have considerable effects on both teaching performance and teachers' overall well-being. Effective preventive strategies, such as vocal hygiene education, noise reduction, and workload adjustments, are essential. Future interventions should be culturally tailored and consider gender-specific needs. Further research is required to explore the underlying health conditions and psychosocial impacts to refine preventive strategies and improve teachers' vocal health and job satisfaction.